Gaming the gamers : using experience maps to develop revenue-generating insights - Grayson, Kent, (SAGE knowledge. Cases., 2016)
A senior product manager for a telecommunications company has been asked to propose ideas for generating new revenue from video gamers who use his company's Internet services. The manager has commissioned the development of 'experience maps' for three subsegments within the gamer segment. The experience maps, which are reproduced in the case, provide students with an opportunity to generate customer insights based on real qualitative data.